ASSESSMENT OF INDUSTRIAL SUSTAINABILITY IN THE HERBAL AND MEDICINE SECTOR - Agustri, Febrina; Destyarini, Normalita; Novira, Diana; Dwyanton, Fertilio (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
The Ministry of Industry of the Republic of Indonesia is committed to increasing the competitive position of industry globally from 41st to 39th in the world out of 138 countries recorded by the 2016-2017 Global Competitiveness Report. Sustainability requires careful planning, namely assessment. The herbal medicine and medicine industry is an industry with significant development, absorbing a workforce of 15 million people and continues to grow along with developments in the direction of food, beverages, cosmetics, spas and aromatherapy. This research aims to develop industrial sustainability assessment indicators implemented in the herbal medicine and medicine sector in the city of Surakarta. The method used is the Delphi method to validate indicators, then MCDM to support the decision making process. The MCDM method used is AHP, which assesses and determines the level of industrial sustainability. Respondents in this study are companies with the criteria for a workforce of more than 100 people and are registered with the Ministry of Industry.